CCTV in Africa: Constructive approach to manufacturing consent. (1st June 2020) - Xiang, Yu; Zhang, Xiaoxing
China Central Television (CCTV) launched its first media centre in Nairobi, Kenya, in 2012 and is one of the main actors in the 'China's media go global' campaign. CCTV-Africa's reporting style has previously been engaged by media practitioners and academics in terms of its discursive practices. In 2014, a new paradigm studying the journalistic practice of Chinese media in Africa emerged. It has been argued that the journalistic approach deployed by Chinese media in Africa, especially CCTV-Africa, is more constructive than simply positive. This article aims to provide a structural analysis on the role of international news in mediating and reinforcing the 'harmony of interest' of transnational elite groups with empirical findings from the case study of CCTV-Africa and its constructive approach of journalism. The findings of this research show that the 'constructiveness' of CCTV-Africa is marked with the 'non-interference' diplomatic strategy of China in Africa which minimalizes the political involvement of China in local conflicts by reducing investigation on causes and emphasizing solutions. Simultaneously, it also produces an apolitical context which encourages economic development in African societies to cater to the grander politics of China in Africa.